Effect of the environment on the electrical conductance of the single benzene-1,4-diamine molecule junction - Nakashima, Shigeto; Takahashi, Yuuta; Kiguchi, Manabu (Beilstein Journal of Nanotechnology, 2011)
We investigated the effect of the environment on the electrical conductance of a single benzene-1,4-diamine (BDA) molecule bridging Au electrodes, using the scanning tunneling microscope (STM). The conductance of the single BDA molecule junction decreased upon a change in the environment from tetraglyme, to mesitylene, to water, and finally to N2 gas, while the spread in the conductance value increased. The order of the conductance values of the single BDA molecule junction was explained by the strength of the interaction between the solvent molecules and the Au electrodes. The order of the spread in the conductance values was explained by the diversity in the coverage of the BDA molecule at metal electrodes and atomic and molecular motion of the single-molecule junction.
Keywords: benzene-1,4-diamine; electric conductance; single-molecule junction; solvent

Molecular Electronics - Cuevas, J. C.; Scheer, E. (World Scientific Publishing, 2010)

(untitled) - Agraït, N.; Yeyati, A. L.; van Ruitenbeek, J. M. (Phys. Rep., 2003)

(untitled) - Tada, T.; Yoshizawa, K. (ChemPhysChem, 2002)

(untitled) - Chen, F.; Li, X.; Hihath, J.; Huang, Z.; Tao, N. (J. Am. Chem. Soc., 2006)

(untitled) - Kiguchi, M.; Miura, S.; Hara, K.; Sawamura, M.; Murakoshi, K. (Appl. Phys. Lett., 2007)

(untitled) - Wu, S.; González, M. T.; Huber, R.; Grunder, S.; Mayor, M.; Schönenberger, C.; Calame, M. (Nat. Nanotechnol., 2008)

(untitled) - Schneebeli, S. T.; Kamenetska, M.; Cheng, Z.; Skouta, R.; Friesner, R. A.; Venkataraman, L.; Breslow, R. (J. Am. Chem. Soc., 2011)

(untitled) - Kiguchi, M.; Takahashi, T.; Takahashi, Y.; Yamauchi, Y.; Murase, T.; Fujita, M.; Tada, T.; Watanabe, S. (Angew. Chem., Int. Ed., 2011)

(untitled) - Dahlke, R.; Schollwöck, U. (Phys. Rev. B, 2004)

(untitled) - Tawara, A.; Tada, T.; Watanabe, S. (Phys. Rev. B, 2009)

(untitled) - Venkataraman, L.; Klare, J. E.; Tam, I. W.; Nuckolls, C.; Hybertsen, M. S.; Steigerwald, M. L. (Nano Lett., 2006)

(untitled) - Dell’Angela, M.; Kladnik, G.; Cossaro, A.; Verdini, A.; Kamenetska, M.; Tamblyn, I.; Quek, S. Y.; Neaton, J. B.; Cvetko, D.; Morgante, A.; Venkataraman, L. (Nano Lett., 2010)